2005
DOI: 10.1016/j.jcrs.2004.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cataract surgery incision location and intraocular lens type on ocular aberrations

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 38 publications
3
23
1
1
Order By: Relevance
“…Pesudovs et al revealed that coma-and spherical-like aberrations for 6-mm pupils in patients with various types of spherical intraocular lenses (IOLs) were 0.37-0.51 and 0.36-0.60, respectively. 31 Oshika et al described that third-and fourth-order RMS in 7-mm pupils were 0.883 and 1.455 after photorefractive keratectomy, respectively, and those after laser in situ keratomileusis were 1.436 and 1.941, respectively. 23 The amount of HOAs after scleral buckling surgery was similar to that after cataract surgery and lower than that after excimer laser refractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Pesudovs et al revealed that coma-and spherical-like aberrations for 6-mm pupils in patients with various types of spherical intraocular lenses (IOLs) were 0.37-0.51 and 0.36-0.60, respectively. 31 Oshika et al described that third-and fourth-order RMS in 7-mm pupils were 0.883 and 1.455 after photorefractive keratectomy, respectively, and those after laser in situ keratomileusis were 1.436 and 1.941, respectively. 23 The amount of HOAs after scleral buckling surgery was similar to that after cataract surgery and lower than that after excimer laser refractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Pesudovs et al 14 studied the effect of 2 types of spherical IOLs (PMMA and acrylic) and incision locations (corneal and scleral) on total wave aberrations, measured with a Hartmann-Shack wavefront sensor. Aberrations in 20 eyes (PMMA IOL, scleral incision), 21 eyes (acrylic IOL, scleral incision), and 16 eyes (acrylic IOL, corneal incision) were compared with those in an age-matched control group.…”
Section: J Cataract Refract Surg 2007; 33:217-226 Q 2007 Ascrs and Escrsmentioning
confidence: 99%
“…However, aberrations in pseudophakic eyes are not solely composed of corneal aberrations but also those of other components including IOLs. [17][18][19][20][21] Thus, it would be more appropriate to use total ocular aberrations for the analysis. In addition, target size is an important factor in the accommodative response.…”
Section: J Cataract Refract Surg 2006; 32:1643-1649 Q 2006 Ascrs and mentioning
confidence: 99%